Pengembangan Media Pembelajaran Realia (Portofolio Fashion Design) pada Elemen Penyusunan Koleksi Busana di SMK Negeri 1 Brondong - Sindi Mariska; Imami Arum Tri Rahayu (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study is motivated by the lack of interesting and innovative learning media in teaching the topic of fashion collection arrangement at SMK Negeri 1 Brondong. In this topic, students still experience difficulties in understanding the material because the concept of a fashion portfolio is still abstract, making it hard for them to visualize the actual form of the designs they are expected to create. As a result, students become less active, less motivated, and the learning process is not optimal since it is still dominated by lecture methods and media such as handouts and PowerPoint. This research aims to develop a realia-based learning media in the form of a fashion design portfolio, as well as to determine the feasibility of the media, student responses, and learning outcomes after using the media. The research method used is Research and Development (R&D) with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages, with the subjects being eleventh-grade students of the Fashion Design and Production program at SMK Negeri 1 Brondong. The results show that the realia-based learning media in the form of a fashion design portfolio is considered feasible based on validation by material and media experts, receives very positive responses from students due to its attractive and easy-to-understand presentation, and is able to improve students’ learning outcomes in the topic of fashion collection arrangement. Therefore, this media can be an effective alternative to make learning more engaging, interactive, and easier for students to understand.